Observation of Complement Protein Gene Expression Before and After Surgery in Opioid-Consuming and Opioid-Naive Patients. (January 2021) - Johnson, Ken B.; Light, Alan R.; Odell, Daniel W.; Stuart, Ami R.; Radtke, Jacob; Light, Kathleen C.
Abstract : Opioids may influence inflammation. We compared genes associated with pain and inflammation in patients who consumed opioids (3–120 mg of oral morphine equivalents per day) with those who did not for differential expression. White blood cells were assayed in 20 patients presenting for total lower extremity joint replacement. We focused on messenger ribonucleic acid expression of complement proteins. We report that the expression of a complement inhibitor, complement 4 binding protein A, was reduced, and the expression of a complement activator, complement factor D, was increased in opioid-consuming patients. We conclude that opioid consumption may influence expression of complement activators and inhibitors.